CASE REPORT: PROGRESSIVE HEADACHE IN A RARE CASE OF MENINGIOMA - Nia Citama Saragih; Feda Anisah Makkiyah; Rosita Alfi Syahrin; Theodora Caroline Sihotang (The Health Researcher's Journal, 2026)
The most prevalent primary tumour of the central nervous system is meningioma, and the incidence increases with age. This tumour can be detected through radiological examination and classified based on the results of anatomical pathology examination. A 48-year-old woman presented to the hospital with complaints of a left-sided progressive headache for several years without any other complaints. Imaging examination showed a lesion in the falx cerebri of the sinistra aspect that suggested typical meningioma. The woman decided to undergo craniotomy resection surgery and histopathological analysis. Based on the WHO classification, the histopathology results revealed a microcystic and chordoidal meningioma. The patient had significant improvement in her symptoms postoperatively, and the tumour size decreased on follow-up imaging. This case report aims to highlight the diagnostic challenges and clinical relevance of identifying progressive headaches as one manifestation of atypical meningioma.